Analysis of Human Resources Planning in PT. Bagus Wijaya Karya Bekasi - Indonesia - Tubagus Achmad Darodjat; Marlon Rael Astillero (Enrichment : Journal of Management, 2020)
Research analysis of Human Resource Planning in this company is done through a qualitative approach based on the principle of appropriateness i.e., observation of documentation and in-depth interviews. The sample in this study consisted of informants (respondents) in key positions in the company, such as supervisors and policy makers in the field.This research was conducted over 4 months. The results of the analysis of this study indicate that human resource planning in this company has been successfully implemented. The use of a periodic program has ensured the procurement of corporate human resources, an effective use of human resources and the successful development and maintenance of human resources